Cervical neoplasia in systemic lupus erythematosus: a nationwide study. (30th December 2016) - Wadström, Hjalmar; Arkema, Elizabeth V.; Sjöwall, Christopher; Askling, Johan; Simard, Julia F.
Abstract: Objective. The aim was to examine the risk of cervical neoplasia in women with SLE, overall and with respect to treatment, compared with women from the general population. Methods. By linking national Swedish registers, we assembled a cohort including women with SLE (n = 4976) and matched general population comparators (n = 29 703). Two subcohorts of treated SLE patients were defined on the basis of treatment with antimalarials (n = 1942) and other immunosuppressants (AZA, CYC, ciclosporin, MTX, MMF or rituximab; n = 2175). The main outcome was defined as a first cervical neoplasia (dysplasia or cancer) during follow-up. Secondary outcomes were first cervical intraepithelial neoplasia (CIN) 1; first CIN grades 2–3; and first invasive cervical cancer during follow-up (2006–12). Cox regression models estimated relative risks adjusted for age, level of education, health-care utilization, number of children, marital status, family history of cervical cancer and prior cervical screening. Results. Based on 121 events of cervical neoplasia during 23 136 person-years among SLE patients, there was an increased risk of any cervical neoplasia compared with the general population [hazard ratio (HR) = 2.12 (95% CI: 1.65, 2.71)]. The risk of CIN 1 [HR = 2.33 (95% CI: 1.58, 3.44)], CIN 2–3 [HR = 1.95 (95% CI: 1.43, 2.65)], but not invasive cervical cancer [HR = 1.64 (95% CI: 0.54, 5.02)], was increased in women with SLE. The subcohort treated with other immunosuppressants was at highest risk of cervical neoplasia. Conclusion. SLE is a risk factor for cervical neoplasia, in particular for pre-malignant cervical lesions. Among patients with SLE, the risk is higher among those treated with immunosuppresants compared with those treated with antimalarials.